Post-mining potentials and redevelopment of former mining regions in Central Europe – Case studies from Germany and Slovenia - Marot, Naja; Harfst, Jörn (Acta geographica Slovenica, 2012)
This article discusses the character of post-mining potentials and their role in regional development in a German and Slovenian mining region. The many possible uses often include renewable energies (biomass, geothermal energy), or tourism (museums). Discussing two case study regions, this article presents similarities and differences in approaches towards the utilisation of potentials, and compares factors that influence utilisation with reference to national framework conditions. The text argues that in the context of structural change and mine closures, the use of post-mining potentials, such as post-mining landscapes, infrastructures and traditions, can be a way to explore new development options for affected regions.